Antitumoral effects of the alkynylphosphonate analogue of calcitriol EM1 on glioblastoma multiforme cells - Ferronato, María Julia (2017)
Glioblastoma multiforme (GBM) is the worst and most common brain tumor, characterized by high proliferation and invasion rates. The current standard treatment is mainly based on chemoradiotherapy and this approach has slightly improved patient survival. Thus, novel strategies aimed at prolonging the survival and ensuring a better quality of life are necessary. In the present work, we investigated the antitumoral effect of the novel analogue of calcitriol EM1 on GBM cells employing in vitro, in silico, and in vivo assays. In vitro, we demonstrated that EM1 treatment selectively decreases the viability of murine and human tumor cells without affecting that of normal human astrocytes. The analysis of the mechanisms showed that EM1 produces cell cycle arrest in the T98G cell line, which is accompanied by an increase in p21, p27, p57 protein levels and a decrease in cyclin D1, p-Akt-S473, p-ERK1/2 and c-Jun expression. Moreover, EM1 treatment also exerts in GBM cells anti-migratory effects and decreases their invasive capacity by a reduction in MMP-9 proteolytic activity. In silico, we demonstrated that EM1 is able to bind to the vitamin D receptor with greater affinity than calcitriol. Finally, we showed that EM1 treatment of nude mice administered at 50 ug/Kg body weight during 21 days neither induces hypercalcemia nor toxicity effects. In conclusion, all the results indicate the potential of EM1 analogue as a promising therapeutic alternative for GBM treatment.